SPAK Deficiency Attenuates Chemotherapy-Induced Intestinal Mucositis - Huang, Tien-Yu; Yang, Sung-Sen; Liao, Ching-Len; Lin, Ming-Hong; Lin, Hsuan-Hwai; Lin, Jung-Chun; Chen, Peng-Jen; Shih, Yu-Lueng; Chang, Wei-Kuo; Hsieh, Tsai-Yuan (Frontiers in Oncology, 2021)
Introduction: Ste20-related protein proline/alanine-rich kinase (SPAK) affects cell proliferation, differentiation, and transformation, and sodium and chloride transport in the gut. However, its role in gut injury pathogenesis is unclear. Objective: We determined the role of SPAK in chemotherapy-induced intestinal mucositis using in vivo and in vitro models. Methods: Using SPAK-knockout (KO) mice, we evaluated the severity of intestinal mucositis induced by 5-fluorouracil (5-FU) by assessing body weight loss, histological changes in the intestinal mucosa, length of villi in the small intestine, pro-inflammatory cytokine levels, proliferative indices, and apoptotic indices. We also evaluated changes in gut permeability and tight junction-associated protein expression. Changes in cell permeability, proliferation, and apoptosis were assessed in SPAK siRNA-transfected 5FU-treated IEC-6 cells. Results: 5-FU-treated SPAK-KO mice exhibited milder intestinal mucositis, reduced pro-inflammatory cytokine expression, increased villus length, good maintenance of proliferative indices of villus cells, decreased apoptotic index of enterocytes, reduced gut permeability, and restoration of tight junction protein expression (vs. 5-FU-treated wild-type mice). Under in vitro conditions, siRNA-mediated SPAK-knockdown in IEC-6 cells decreased cell permeability and maintained homeostasis following 5-FU treatment. Conclusion: SPAK deficiency attenuated chemotherapy-induced intestinal mucositis by modulating gut permeability and tight junction-associated protein expression, and maintaining gut homeostasis in murine small intestinal tissues following gut injury. The expression of SPAK may influence the pathogenesis of chemotherapy-induced intestinal mucositis.